Pengaruh Pemahaman Nilai-Nilai Pancasila terhadap Kehidupan Berdemokrasi Mahasiswa - Ciciria, Deri; Kesuma, Tubagus Ali Rachman Puja; Hafidz, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
Higher education must become a strategic ecosystem in developing Pancasila values ​​to regenerate student democratic life. The purpose of this study was to find out and describe the influence of understanding Pancasila values ​​on the democratic life of STKIP PGRI Bandar Lampung students. This research involved 358 students spread across 7 (seven) study programs. This research is a quantitative descriptive study using the correlational method. The instrument of Pancasila values ​​was adopted from the embodiment of the socialization material